Magnetic mediation effect of a C impurity in a Mn-doped Zn12O12 nanocluster: a case of multiple exchange interactions. (3rd August 2015) - Ma, X G; Liu, Y F; Liu, N; Ren, J C; Xu, G W; Chu, L; Lv, H; Huang, C Y; Zhu, Y F
Abstract: The stability and exchange interaction mechanism of a doped Zn12 O12 cluster with Mn and C atoms were investigated by first-principles calculations. For the Mn-doped Zn12 O12 cluster, it is identified that a superexchange interaction deriving the hybridization between the Mn and O 2p xy orbitals dominates the Mn(↑)–Mn(↓) antiferromagnetic coupling, although a direct exchange interaction deriving the Mn–Mn bonding is also found. In order to turn the Mn spin state in the Mn-doped Zn12 O12 cluster, C doping is undertaken to change the magnetic interactions of these impurities. It is proved that the C incorporation into the Mn-doped Zn12 O12 cluster destroys the short-ranged antiferromagnetic coupling, where multiple exchange interactions take over, including the direct exchange interaction and the kinetic p-d exchange interaction partially due to the geometric distortion and surface effect with dangling bonds (sp 2 -like hybrids). It is concluded that the kinetic p-d exchange interaction plays a dominant role in Mn/C-doped Zn12 O12 clusters.